The Level of D-Dimer Is Positively Correlated With the Severity of Mycoplasma pneumoniae Pneumonia in Children - Zheng, Yan; Hua, Lingling; Zhao, Qiannan; Li, Mengyao; Huang, Meixia; Zhou, Yunlian; Wang, Yingshuo; Chen, Zhimin; Zhang, Yuanyuan (Frontiers in Cellular and Infection Microbiology, 2021)
Objective Mycoplasma pneumoniae pneumonia (MPP) is an important disease in children. Studies have demonstrated that the levels of D-dimer are elevated in some children with MPP, especially those with thrombotic complications. However, the potential association between MPP and D-dimer remains unclear. In our study, we sought to explore the relationship between the levels of plasma D-dimer and clinical characteristics of MPP patients. Methods Retrospective analysis was conducted on 356 patients who were hospitalized in our hospital for MPP between January 1, 2017, and December 31, 2019. According to the peak value of D-dimer, patients were divided into three groups: the normal group (D-dimer<0.55 mg/L), the mild-moderately elevated group (D-dimer 0.55–5.5 mg/L) and the severely elevated group (D-dimer >5.5 mg/L). The demographic and clinical information, radiological findings, laboratory data, and treatments of patients were compared among different groups. Results 106 patients were in the normal group, 204 patients were in the mild-moderately elevated group, and 46 patients were in the severely elevated group. More severe clinical and radiographic manifestations, longer length of fever, hospital stay and antibiotic therapy duration, higher incidences of extra-pulmonary complications, refractory MPP (RMPP), severe MPP (SMPP) were found in the elevated group, when compared with the normal group (P<0.01). Meanwhile, we found that the percentage of neutrophil (N%) and CD8+ lymphocyte (CD8+%), C-reactive protein (CRP), lactate dehydrogenase (LDH), interleukin (IL)-6, IL-10, and interferon-gamma (IFN-γ) trended higher with increasing D-dimer, whereas the percentage of lymphocyte (L%) and prealbumin (PAB) trended lower (P<0.01). In addition, the proportions of patients requiring oxygen therapy, glucocorticoid, bronchoscopy, immunoglobulin use, thoracentesis, or ICU admission were significantly higher in the severely elevated group than those in the other two groups (P<0.01). Correlation analysis showed that N%, L%, CRP, LDH, IL-10, length of fever, length of stay, and length of antibiotic therapy had strong correlations with the level of D-dimer. Conclusions MPP patients with higher levels of D-dimer had more severe clinical manifestations and needed longer duration of treatment, which might be closely related to the severity of lung inflammation after MP infection.